Biochar standardization and legislation harmonization. Issue 2 (3rd April 2017) - Meyer, Sebastian; Genesio, Lorenzo; Vogel, Ines; Schmidt, Hans-Peter; Soja, Gerhard; Someus, Edward; Shackley, Simon; Verheijen, Frank G. A.; Glaser, Bruno
Abstract: It is a relatively new concept to use biochar as soil amendment and for climate change mitigation. For this reason, the national and supranational legislation in the EU is not yet adequately prepared to regulate both the production and the application of biochar. Driven by this "regulatory gap", voluntary biochar quality standards have been formed in Europe with the European Biochar Certificate, in the UK with the Biochar Quality Mandate and in the USA with the IBI Standard which is intended to be used internationally. In parallel to this, biochar producers and biochar users in a number of EU countries were partly successful in fitting the new biochar product into the existing national legislation for fertilisers, soil improvers and composts. The intended revision of the EC Regulation 2003/2003 on fertilisers offers the opportunity to regulate the use of biochar at the EU level. This publication summarizes the efforts on biochar standardization which have been carried out by voluntary products standards and illustrates existing legislation in EU member states, which apply to the production and use of biochar. It describes existing and planned EU regulations, which impact biochar applications and it develops recommendations on the harmonization of biochar legislation in the EU.